Corporate governance awareness and disclosure practices among Malaysian SMEs: preliminary findings - Noor Kaziemah Sariman; Rozaidy Mahadi; Junainah Jaidi (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2024)
Corporate governance (CG) is increasingly recognized as a vital driver of transparency, accountability, and business sustainability. While substantial attention has been given to CG practices in large corporations, there remains a significant gap in understanding how microenterprises, small and medium-sized enterprises (SMEs) in developing countries, particularly Malaysia, perceive and implement corporate governance. This study explores the level of corporate governance awareness and disclosure among Malaysian SMEs, focusing on key areas such as board structure, role separation between CEO and chairman, audit committees, and CG disclosure in annual reports. Using data from a survey of 56 SMEs, the findings reveal significant gaps in corporate governance awareness, a lack of formal governance structures, and limited disclosure of governance practices. The study identifies critical barriers to the adoption of good corporate governance practices among Malaysian SMEs and suggests avenues for future research to address these gaps.